Pengaruh Good Corporate Governance terhadap Kinerja Perusahaan pada Sektor Keuangan - Melia, Agustina (Business Accounting Review, 2015)
This study aimed to examine the effect of good corporate governance on firm performance in finance sector company. This study used board of commissioner, independent commissioner, and managerial ownership as good corporate governanceâs proxy on the firm performance. Board of commissioner, independent commissioner, and managerial ownership used as independent variables. The firm performance used in this study using ROA as measurement and dependent variable. This study also used variable control which was firm size. Samples used in this study was finance sector company of the period of 2011-2013. The hypothesis was tested by using multiple regression linear. Simultaneously, board of commissioner, independent commissioner, managerial ownership, and firm size significantly affected the ROA. Partially, board of commissioner and managerial ownership didnât significantly affect the ROA. Meanwhile, independent commissioner and firm size negatively and significantly affect the ROA.